Perceptions of adult Arkansans regarding trusted sources of information about the COVID-19 pandemic - Rachel S. Purvis; Don E. Willis; Ramey Moore; Cari Bogulski; Pearl A. McElfish (BMC, 2021)
Abstract Background The United States leads the world in confirmed COVID-19 cases; Arkansas ranks fifth in average daily cases per 100,000. Historically, Americans relied on health communications from governmental sources and the news media. However, there has been a documented decline of trust in these sources. The present study seeks to understand trusted sources of information about COVID-19 to improve health messaging because research shows the level of trust is associated with adherence to recommendations. Methods Data were collected using an online survey from participants (N = 1221) who were 18 years of age or older and residing, employed, or accessing health care in Arkansas. A qualitative descriptive design was used to summarize participants' experiences and perceptions related to trusted sources of COVID-19 information. Results Two primary themes related to participants' perceptions of sources of information about COVID-19 are reported: 1) trusted sources of information and 2) distrust or lack of trust in sources of information. Several subthemes emerged within each primary theme. Results showed high trust in the academic medical center, federal and state public health agencies, and local health care providers. The study also documents diverging voices of distrust and uncertainty in making sense of contradictory information. Participants reported the main reason for their lack of trust was the rapidly changing information and the lack of consistency in information provided across sources. Conclusions This finding provides insight into the importance of coordination between national, state, and local communications to bolster trust. Personal recommendations and testimonies from trusted health care providers and professionals could inform public health messaging interventions to increase vaccine uptake.